3D Model Visualization and Interaction Using a Cubic Fiducial Marker - Rabbi, Ihsan; Ullah, Sehat (Augmented and Virtual Reality, 2014)
Fiducial markers are generally used for tracking the camera position and orientation in augmented reality applications. The tracking performance of existing markers degrades due to marker occlusion. Similarly it does not support 3600 rotation in all axes and consequently it becomes difficult to achieve realistic/intuitive manipulation & visualization of virtual objects/contents. This paper presents the applications of a cubic marker in 3D models visualization and interaction and overcomes the above challenges. A cube having six fiducial markers, each on its face is used to be tracked from a single camera. The corners of the cubic marker are used to find its center. A 3D model is visualized on the center point of the real cubic maker. This cubic marker produces robust tracking results during occlusion. The visualization of 3D virtual models and interaction with these models are more realistic and ergonomic using the cubic marker.